Stated Preferences for Firm's Characteristics and Asset Allocation Decisions. Issue 4 (August 2019) - Khan, Mohammad Tariqul Islam; Tan, Siow-Hooi
Abstract: The present article investigates the relationship between stated preferences for firm's characteristics and asset allocation decisions. Data from the survey of retail investors in Malaysia are used for estimations by employing binary logit and ordered logistic models. The analyses show that preferences for a firm's value characteristics, quality of management and product characteristics, risky characteristics, liquidity and trading volume characteristics affect holding of a particular financial asset, number of asset holding, quite diversified portfolio holding and hypothetical asset allocation. However, a firm's characteristics have no influence on fully diversified portfolio. In Malaysia, the regulators may consider the investor's preferences for specific firm's characteristics in designing policies to reduce the apparent structural imbalance in the capital market.